2004
DOI: 10.1021/es0350583
|View full text |Cite
|
Sign up to set email alerts
|

Emission Rates of Particulate Matter and Elemental and Organic Carbon from In-Use Diesel Engines

Abstract: Elemental carbon (EC), organic carbon (OC), and particulate matter (PM) emission rates are reported for a number of heavy heavy-duty diesel trucks (HHDDTs) and back-up generators (BUGs) operating under real-world conditions. Emission rates were determined using a unique mobile emissions laboratory (MEL) equipped with a total capture full-scale dilution tunnel connected directly to the diesel engine via a snorkel. This paper shows that PM, EC, and OC emission rates are strongly dependent on the mode of vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
134
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(151 citation statements)
references
References 19 publications
15
134
0
2
Order By: Relevance
“…Particles released directly from a source (primary PM) have a characteristic size and composition distribution that is determined by the generating mechanism (Hildemann et al 1991;Kleeman et al 1999;Kleeman et al 2000;Allen et al 2001;Wingfors et al 2001;McDonald et al 2003;Sturm et al 2003;Hays 2004;Laschober et al 2004;McDonald et al 2004;Shah et al 2004). Once in the atmosphere, the particle size and composition distribution can be modified by chemical reactions, condensation/evaporation of semi-volatile species, coagulation with other particles, activation during high humidity, wet deposition, and dry deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Particles released directly from a source (primary PM) have a characteristic size and composition distribution that is determined by the generating mechanism (Hildemann et al 1991;Kleeman et al 1999;Kleeman et al 2000;Allen et al 2001;Wingfors et al 2001;McDonald et al 2003;Sturm et al 2003;Hays 2004;Laschober et al 2004;McDonald et al 2004;Shah et al 2004). Once in the atmosphere, the particle size and composition distribution can be modified by chemical reactions, condensation/evaporation of semi-volatile species, coagulation with other particles, activation during high humidity, wet deposition, and dry deposition.…”
Section: Introductionmentioning
confidence: 99%
“…where the 1.2 accounts for hydrogen and oxygen present in the OC; EC and OC refer to the mass of EC and OC collected [5]. In this paper, the PM mass was calculated as the addition of CM and the mass of water-soluble ions.…”
Section: Pm Sampling and Composition Analysismentioning
confidence: 99%
“…At low load, the exhaust temperature was lower compared to that at high load, thus the OC fraction in PM was higher at low load. Shah et al also reported that the OC fraction in TC was higher at idle than at creep: 0.80 OC/EC at idle and 21.80 at creep [5]. A blend of 20% biodiesel with diesel fuel (B20) was prepared and tested at 25%, 50%, and 75% load of 2690 r$min -1 .…”
Section: Pm Sampling and Composition Analysismentioning
confidence: 99%
See 2 more Smart Citations